(untitled) (MAUSAM, 1966)
An attempt has been made for making a study of human comfort of 27 stations in India using the strain chart of Lee. Using the mean monthly temperature and vapour pressure data of these stations, climograms were drawn on the strain chart and comfort for each individual month of the year, of the stations is determined.